(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: The role of preterm birth in contributing to the neonatal’s worldwide mortality and morbidity, remains one of the leading causes. The use of antenatal corticosteroids (ACS) greatly enhances the fetal lung maturation and decreases the incidence of these problems in newborns born before 37 weeks of gestation. In spite of the proven efficacy of ACS, there are still unresolved and many debated questions pertaining to the timing, dosing, and merits and risks in certain population subsets, especially in multiple gestations and late preterm births. Methodology: Including primary research studies like RCTs, cohorts, and observational studies examining the effectiveness of ACS on the reduction of early neonatal morbidity and preterm births, is part of this systematic review. All studies included in this review underwent a detailed search of electronic data bases such as PubMed, Embase and the Cochrane Library. Only the studies published in the English language were incorporated. Based on the predetermined inclusion criteria, the selected data captured study type, the targeted population, the intervention, as well as any significant neonatal outcomes. Results: Examination of 19 RCTs and numerous big cohort and observational studies showed that in preterm newborns, a single course of ACS significantly lowers the incidence of RDS, IVH, NEC, and neonatal death especially when given within 17 days before birth. The benefit was seen as early as two hours after administration and lasted up to two weeks. Though several courses of ACS did not yield extra benefits and were linked to lower birth weight and head circumference, a single course was still successful among varied maternal and neonatal subgroups. ACS lowered respiratory morbidity but raised the risk of newborn hypoglycemia in late preterm and early term populations. ACS was effective across several gestations and unaffected by maternal BMI. Conclusion: Antenatal corticosteroids are quite successful in lowering neonatal morbidity and mortality in preterm births; the most benefit comes from doses just before delivery. The data favors the regular application of a single ACS class in women between 24 and 34 weeks gestation who are at danger of preterm birth. Regarding recurring courses and use in late preterm or early term pregnancies, where advantages have to be weighed against possible dangers including hypoglycemia and growth restriction, caution is advised.